POSITIVE PSYCHOLOGY AND COVID-19: experience report of the extension project “LAPPOT in Quarantine” (Citizenship in Action: Extension and Culture Magazine, 2023)
Since beginning, the COVID-19 pandemic has generated changes in daily life. Among the measures adopted was the implementation of quarantine with isolation and social distance, which marked not only the decrease in human interactions, but the increase in feelings and sometimes negative experiences related to the lack of it, fear and difficulty in adapting and implement new behaviors. With this in mind, researchers from the Laboratory of Positive Psychology in Organizations and at Work (LAPPOT) at the Federal University of Santa Catarina (UFSC) developed an extension project with the objective of helping the population through the dissemination of knowledge and coping strategies based on the principles of Positive Psychology. This article aims to present the experience report with the description of the project, the method, the execution and the results obtained with its application. The project took place by conducting lives in the laboratory’s network and social media with the aim of disseminating knowledge about positive psychology to contribute to situations of isolation and social distance due to the Covid-19 pandemic. The actions carried out by the extension project helped to develop strategies aimed at promoting health through emotions, feelings, attitudes and behaviors that favored people's well-being, quality of life and happiness.
Keywords: Positive Psychology.; Mental health.; COVID-19.; Community-Institutional Relations.; Quarantine.